The Forest and the EcoGothic - Parker, Elizabeth. author. aut Link
IX, 308 p. 2 illus.
Keywords: ‘This is a rigorously researched, wide-ranging and original study with international reach and significance. It makes a very important contribution to the Gothic field.’ – Catherine Wynne, Reader in English, University of Hull ‘I could not recommend this book more strongly. It is truly exceptional: thoroughly researched, effectively structured, convincingly argued, containing always-insightful readings of a dizzying array of film and fiction, and beautifully written. This is ground-breaking, important work.’ – Dawn Keetley, Professor of English, Lehigh University This book offers the first full length study on the pervasive archetype of The Gothic Forest in Western culture. The idea of the forest as deep, dark, and dangerous has an extensive history and continues to resonate throughout contemporary popular culture. The Forest and the EcoGothic examines both why we fear the forest and how exactly these fears manifest in our stories. It draws on and furthers the nascent field of the ecoGothic, which seeks to explore the intersections between ecocriticism and Gothic studies. In the age of the Anthropocene, this work importantly interrogates our relationship to and understandings of the more-than-human world. This work introduces the trope of the Gothic forest, as well as important critical contexts for its discussion, and examines the three main ways in which this trope manifests: as a living, animated threat; as a traditional habitat for monsters; and as a dangerous site for human settlement. This book will appeal to students and scholars with interests in horror and the Gothic, ecohorror and the ecoGothic, environmentalism, ecocriticism, and popular culture more broadly. The accessibility of the subject of ‘The Deep Dark Woods’, coupled with increasingly mainstream interests in interactions between humanity and nature, means this work will also be of keen interest to the general public.